Caregiver worry about COVID-19 as a predictor of social mitigation behaviours and SARS-CoV-2 infection in a 12-city U.S. surveillance study of households with children - Steven M. Brunwasser; Tebeb Gebretsadik; Anisha Satish; Jennifer C. Cole; William D. Dupont; Christine Joseph; Casper G. Bendixsen; Agustin Calatroni; Samuel J. Arbes, Jr; Patricia C. Fulkerson; Joshua Sanders; Leonard B. Bacharier; et al. (Preventive Medicine Reports)
Objective: Understanding compliance with COVID-19 mitigation recommendations is critical for informing efforts to contain future infectious disease outbreaks. This study tested the hypothesis that higher levels of worry about COVID-19 illness among household caregivers would predict lower (a) levels of overall and discretionary social exposure activities and (b) rates of household SARS-CoV-2 infections. Methods: Data were drawn from a surveillance study of households with children (N = 1913) recruited from 12 U.S. cities during the initial year of the pandemic and followed for 28 weeks (data collection: 1-May-2020 through 22-Feb-2021). Caregivers rated how much they worried about family members getting COVID-19 and subsequently reported household levels of outside-the-home social activities that could increase risk for SARS-CoV-2 transmission at 14 follow-ups. Caregivers collected household nasal swabs on a fortnightly basis and peripheral blood samples at study conclusion to monitor for SARS-CoV-2 infections by polymerase chain reaction and serology. Primary analyses used generalized linear and generalized mixed-effects modelling. Results: Caregivers with high enrollment levels of worry about COVID-19 illness were more likely to reduce direct social contact outside the household, particularly during the U.S.'s most deadly pandemic wave. Households of caregivers with lower COVID-19 worry had higher odds of (a) reporting discretionary outside-the-home social interaction and (b) SARS-CoV-2 infection. Conclusions: This was, to our knowledge, the first study showing that caregiver COVID-19 illness worry was predictive of both COVID-19 mitigation compliance and laboratory-determined household infection. Findings should inform studies weighing the adaptive value of worrying about infectious disease outbreaks against established detrimental health effects.